2013
DOI: 10.3892/ol.2013.1214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colonoscopy in the diagnosis and treatment of rectal carcinoid tumors with diameter less than 1 cm in 21 patients

Abstract: The aim of this study was to evaluate colonoscopy in the diagnosis and treatment of rectal carcinoid tumors with diameter <1 cm. Elevated lesions with normal mucosal appearance under colonoscopy were identified. Endoscopic ultrasound (EUS) was performed in 16 patients. Lesions diagnosed as rectal carcinoid tumors were resected by endoscopic mucosal resection (EMR). The diagnosis of specimens by EMR was confirmed by pathological examination. Immunohistochemical staining was undertaken and follow-up data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…None of the lesions penetrated the submucosa or showed adjacent lymph node metastasis. Some studies reported that rectal NETs ≤10 mm in size that were examined by EUS before endoscopic resection were correctly diagnosed as confined to the submucosa (6,14,20). Although EUS is a useful method for evaluating the depth of invasion, its necessity is questionable in cases of rectal NETs ≤10 mm in size.…”
Section: Discussionmentioning
confidence: 99%
“…None of the lesions penetrated the submucosa or showed adjacent lymph node metastasis. Some studies reported that rectal NETs ≤10 mm in size that were examined by EUS before endoscopic resection were correctly diagnosed as confined to the submucosa (6,14,20). Although EUS is a useful method for evaluating the depth of invasion, its necessity is questionable in cases of rectal NETs ≤10 mm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasonography is used to determine the depth of the invasion, which is a very important variable in the case of a local resection. 9 The invasion or non-invasion of the muscular mucosa determines whether endoscopic excision is sufficient or if surgery is necessary in cases of endoscopically resected rectal carcinoids. It is generally indicated that lesions smaller than 1 cm in diameter can be adequately treated by endoscopic resection in case of negative margins after histological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally indicated that lesions smaller than 1 cm in diameter can be adequately treated by endoscopic resection in case of negative margins after histological evaluation. 2,9,10 Another approach is transanal local excision, as 75% of rectal tumors are located in the mid-and lower thirds of the rectum. Anterior abdominal resection or abdomino-perineal amputation of the rectum have also been indicated in lesions larger than 2 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, rectal NENs are increasingly frequently detected, with the widespread availability and accessibility of endoscopy and cross-sectional imaging modalities (Kos-Kudla et al, 2017). Multiple studies have shown that endoscopic ultrasound (EUS) is an advanced endoscopic technique and is currently used in the diagnosis and preoperative assessment of NENs (Kim, 2012;Liu et al, 2013;Zhang et al, 2017). However, EUS imaging of rectal NEN and differential diagnosis with other submucosal tumors (SMTs) has not been adequately reported.…”
mentioning
confidence: 99%